Genomics and society : ethical, legal, cultural and socioeconomic implications - Kumar, Dhavendra; Chadwick, Ruth (Amsterdam : Academic Press, an imprint of Elsevier, 2016)
Genomics and Society; Ethical, Legal-Cultural, and Socioeconomic Implications is the first book to address the vast and thorny web of ELSI topics identified as core priorities of the NHGRI in 2011. The work addresses fundamental issues of biosociety and bioeconomy as the revolution in biology moves from research lab to healthcare system. Of particular interest to healthcare practitioners, bioethicists, and health economists, and of tangential interest to the gamut of applied social scientists investigating the societal impact of new medical paradigms, the work describes a myriad of issues around consent, confidentiality, rights, patenting, regulation, and legality in the new era of genomic medicine.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed November 6, 2015).
Elsevier
Keywords: Medical genetics; Genomics; Medical genetics -- Social aspects; Medical genetics -- Moral and ethical aspects; Genomics -- Social aspects; Genomics -- Moral and ethical aspects; BUSINESS & ECONOMICS / Business Ethics; Electronic books